2022
DOI: 10.7759/cureus.21331
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Chlamydia Trachomatis in the Pathogenesis of Cervical Cancer

Abstract: Chlamydia trachomatis (CT) is an obligate intracellular, Gram-negative bacterium that causes a variety of infections in both humans and animals. It is the causative agent of one of the most common sexually transmitted infections (STIs) with sequelae such as pelvic inflammatory disease, ectopic pregnancy, and infertility. Furthermore, Chlamydia infections have been epidemiologically linked to cervical cancer (CC) in patients with human papillomavirus (HPV) coinfection. However, a molecular mechanism linking Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Some other authors have also found a relationship between Uu and HPV infection. Their results suggest that Uu infection increases the risk of HPV infection, which may have a synergistic effect on the development of HPV-related cervical dysplasia [ 14 , 16 , 17 ]. It has always been controversial whether Ureaplasma can be considered colonization or infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other authors have also found a relationship between Uu and HPV infection. Their results suggest that Uu infection increases the risk of HPV infection, which may have a synergistic effect on the development of HPV-related cervical dysplasia [ 14 , 16 , 17 ]. It has always been controversial whether Ureaplasma can be considered colonization or infection.…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off value of more than 10 4 CCU/mL Uu in a sample is an additional criterion to distinguish colonization from infection, and Kim et al also indicated that only a Uu with ≥ 10 4 CCU/mL was significantly associated with HPV infection. They also found this relationship in asymptomatic women and, based on this, they recommended HR-HPV testing for women with Uu infection, regardless of symptom status because of a possible synergistic effect between Ureaplasma and HPV in cervical dysplasia caused by HPV [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia trachomatis is a gram-negative bacterium and a prevalent cause of curable sexually-transmitted bacterial infections (STIs) worldwide [ 86 ]. The infection presents as urethritis in men and endocervicitis in women [ 87 ].…”
Section: The Link Between Bacterial Infection and The Onset Of Cancermentioning
confidence: 99%
“…The infection presents as urethritis in men and endocervicitis in women [ 87 ]. Persistent Chlamydia infections have also been identified as a risk factor for developing cervical carcinoma [ 87 ], especially in patients with the human papillomavirus (HPV) coinfection [ 86 , 88 ]. Recent elaborate meta-analysis studies have also corroborated the link between C. trachomatis and cervical cancer [ 89 ].…”
Section: The Link Between Bacterial Infection and The Onset Of Cancermentioning
confidence: 99%
See 1 more Smart Citation